COMPLETE INTUITIONISTIC TEMPORAL LOGICS FOR TOPOLOGICAL DYNAMICS. (4th September 2022) - BOUDOU, JOSEPH; DIÉGUEZ, MARTÍN; FERNÁNDEZ-DUQUE, DAVID
Abstract: The language of linear temporal logic can be interpreted on the class of dynamic topological systems, giving rise to the intuitionistic temporal logic ITL^c_, recently shown to be decidable by Fernández-Duque. In this article we axiomatize this logic, some fragments, and prove completeness for several familiar spaces.